Kinome-wide CRISPR-Cas9 screens revealed EXOSC10 as a positive regulator of TGF-β signaling - Dingding Wang; Xinhao Zhang; Jianxun Guo; Weijia Liu; Yanchi Zhou; Renxian Wang (Biochemistry and Biophysics Reports)
The TGF-β signaling pathway is closely associated with human health and disease, and the systematic identification of factors involved in the TGF-β signaling pathway significantly contributes to the understanding and treatment of various diseases. Through kinome-wide CRISPR screen, we identified 13 candidate regulatory targets. Notably, the well-known hallmark genes TGFBR1 and TGFBR2 emerged as the top two candidate targets. OXSR1 and EXOSC10 were ranked third and fourth as positive candidate targets, respectively, with EXOSC10 being a novel discovery. Importantly, our findings revealed the down-regulation of OXSR1 and EXOSC10 using CRISPR knockout and RNAi technology effectively suppressed the TGF-β signaling pathway in HeLa and HaCaT cells, providing new insights of TGF-β signaling.